INOVASI PENGERING MEKANIS KOPI BERBASIS ARDUINO UNO PADA WILAYAH PETANI KOPI KECAMATAN PEMATANG SIDAMANIK KABUPATEN SIMALUNGUN - Dian, Rahmad; Mulyara, Budi; Siregar, Ratu Mutiara; Maisarah, Maisarah; Dibisono, Muhammad Yusuf; Guntoro, Guntoro (Penerbit Widina, Widina Media Utama, 2024)
Coffee as one of Indonesia's plantation commodities that has very good development potential, considering that coffee consumption in Indonesia is still very high. Currently, the problem that occurs in Simalungun Regency is the conventional drying technology which is at risk of inconsistency in quality and taste so it needs to be fixed and given a solution. The partner team is the Mitra Sejati Jaya Cooperative, where community service activities are carried out in the Sait Buttu area, Pematang Sidamanik District, Simalungun Regency, North Sumatra which is one of the locations for planting Arabica coffee. The purpose of this activity is to create intelligent IT-based appropriate tools and technologies, namely the ARDUINO UNO Smart Sweetener as a solution to the problems of partners and coffee processing community groups, then improve coffee farmers in supporting improvements in the quality of Arabica coffee taste through efficient, portable, and environmentally friendly smart drying technology. The solution that can be provided is in the form of community service activities carried out by a team of lecturers and students from the Institut Teknologi Sawit Indonesia (ITSI) in the form of extension methods, socialization and education related to the technical innovation of the tool called the ARDUINO UNO Smart Sweetener. This community service activity was carried out for ±60 days consisting of the preparation stage consisting of a survey of completeness and preparation, assembly and finishing and pre-test, socialization and education and implementation of community service activities by ITSI lecturers and students. The activity was attended by people who are members of the Coffee Farmers, the Mitra Sejati Jaya cooperative partner team, local residents, lecturers from ITSI and supported by ITSI students. The results of this community service activity were able to educate the community in the Innovation of Mechanical Coffee Dryers.ABSTRAKKopi sebagai salah satu komoditas Perkebunan Indonesia yang memiliki potensi pengembangan masih sangat baik, mengingat konsumsi kopi di Indonesia masih sangat tinggi. Saat ini, permasalahan yang terjadi di Kabupaten Simalungun ialah teknologi pengeringan yang masih konvensional yang beresiko terhadap inkonsistensi mutu dan cita rasa sehingga perlu dibenahi dan diberi solusi. Tim mitra adalah Koperasi Mitra Sejati Jaya, dimana kegiatan pengabdian masyarakat dilaksanakan di daerah Sait Buttu, Kecamatan Pematang Sidamanik, Kabupaten Simalungun, Sumatera Utara yang merupakan salah satu lokasi penanaman kopi arabika. Tujuan dari kegiatan ini dapat menciptakan alat dan teknologi tepat guna yang cerdas berbasis IT yaitu Pemanis Pintar ARDUINO UNO sebagai solusi atas permasalahan mitra dan kelompok masyarakat pengolah kopi, kemudian meningkatkan petani kopi dalam mendukung perbaikan mutu cita rasa kopi arabika melalui teknologi pengeringan pintar yang efisien, portable, dan ramah lingkungan. Solusi yang dapat diberikan yaitu berupa kegiatan pengabdian masyarakat yang dilakukan oleh tim dosen dan mahasiswa Institut Teknologi Sawit Indonesia (ITSI) berupa metode penyuluhan, sosialisasi dan edukasi terkait teknis inovasi alat yang disebut Pemanis Pintar ARDUINO UNO. Kegiatan pengabdian masyarakat ini dilaksanakan selama ±60 hari yang terdiri dari tahap persiapan yang terdiri atas survei kelengkapan dan preparasi, perakitan dan finishing serta pra uji, sosialisasi dan edukasi serta pelaksanaan kegiatan pengabdian kepada masyarakat oleh dosen serta mahasiswa ITSI. Kegiatan dihadiri oleh orang yang tergabung dalam Petani Kopi, Tim mitra koperasi Mitra Sejati Jaya, warga setempat, dosen dari ITSI serta didukung oleh mahasiswa ITSI. Hasil dari kegiatan pengabdian masyarakat ini mampu mengedukasi masyarakat dalam Inovasi Alat Pengering Mekanis Kopi.